3D-printed mesoporous bioactive glass/GelMA biomimetic scaffolds for osteogenic/cementogenic differentiation of periodontal ligament cells - Mei, Nianrou; Wu, Yiwen; Chen, Binglin; Zhuang, Tian; Yu, Xinge; Sui, Baiyan; Ding, Tingting; Liu, Xin (Frontiers in Bioengineering and Biotechnology, 2022)
Integrated regeneration of periodontal tissues remains a challenge in current clinical applications. Due to the tunable physical characteristics and the precise control of scaffold microarchitecture, three-dimensional (3D) printed gelatin methacryloyl (GelMA) based scaffold has emerged as a promising strategy for periodontal tissue regeneration. However, the optimization of the printing biomaterial inks formulation and the relationship between the composition and structures of the printed scaffolds and their comprehensive properties (e.g. mechanical strength, degradation, biological behaviors) remains unclear. Herein, in this work, a novel mesoporous bioactive glass (BG) /GelMA biomimetic scaffold with a large pore size (~400 μm) was developed by extrusion-based 3D printing. Our results showed that the incorporation of mesoporous bioactive glass nanoparticles (BG NPs) significantly improved shape fidelity, surface roughness and bioactivity of 3D printed macroporous GelMA scaffolds, resulting in the enhanced effects on cell attachment and promoting osteogenic/cementogenic differentiation in human periodontal ligament cells. The excellent maintenance of macropore structure, the visibly improved cells spreading, the release of bioactive ions (Si4+, Ca2+), the upregulation of gene expression of osteogenesis and cementogensis, the increase in alkaline phosphatase (ALP) activity and calcium nodules suggested BG NPs could endow GelMA based scaffolds with excellent structural stability and the ability to promote osteogenic/cementogenic differentiation. Our findings demonstrated the great potential of the newly formulated biomaterial inks and biomimetic BG/GelMA scaffolds for being used in periodontal tissue regeneration and provide important insights into the understanding of cell-scaffold interaction in promoting regeneration of functional periodontal tissues.